2018
DOI: 10.2337/dc18-0422
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fucosylated Glycans and C-Reactive Protein as Biomarkers of HNF1A-MODY in Young Adult–Onset Nonautoimmune Diabetes

Abstract: OBJECTIVEMaturity-onset diabetes of the young (MODY) due to variants in HNF1A is the most common type of monogenic diabetes. Frequent misdiagnosis results in missed opportunity to use sulfonylureas as first-line treatment. A nongenetic biomarker could improve selection of subjects for genetic testing and increase diagnosis rates. We previously reported that plasma levels of antennary fucosylated N-glycans and high-sensitivity C-reactive protein (hs-CRP) are reduced in individuals with HNF1A-MODY. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 39 publications
6
76
0
Order By: Relevance
“…Studies of N-glycosylation changes have demonstrated their potential for identifying individuals at an increased risk of type 2 diabetes development [39], indicating that interindividual variation in protein glycosylation might be a novel risk factor in diabetes. Furthermore, it has been shown that it is possible to distinguish individuals with different types of diabetes based on their N-glycome data, as it is the case for the HNF1A-MODY and its differentiation from other common and rare types of diabetes [38,42]. N-glycan branching on T cells has been implicated in the development of type 1 diabetes, and N-glycan branching on glucose transporter has been implicated in the development of type 2 diabetes [23,43,44,73,105].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of N-glycosylation changes have demonstrated their potential for identifying individuals at an increased risk of type 2 diabetes development [39], indicating that interindividual variation in protein glycosylation might be a novel risk factor in diabetes. Furthermore, it has been shown that it is possible to distinguish individuals with different types of diabetes based on their N-glycome data, as it is the case for the HNF1A-MODY and its differentiation from other common and rare types of diabetes [38,42]. N-glycan branching on T cells has been implicated in the development of type 1 diabetes, and N-glycan branching on glucose transporter has been implicated in the development of type 2 diabetes [23,43,44,73,105].…”
Section: Discussionmentioning
confidence: 99%
“…Both antennary fucosylated N‐glycans and hs‐CRP enabled differentiation of individuals with damaging HNF1A alleles; both biomarkers performed better in selecting subjects for genetic testing than classical clinical criteria or the MODY probability calculator . These results imply that it may be possible to identify individuals with a high risk of having damaging HNF1A allele based on glycan biomarkers .…”
Section: Other Types Of Diabetesmentioning
confidence: 92%
See 1 more Smart Citation
“…We assessed predicted pathogenicity using established in silico tools, in line with the American College of Medical Genetics classification (10) and as previously described (11). For structural analysis, we used FoldX (12), introducing variants p.A251T and a nearby MODY-causing mutation, p.V246 L (13), into the structure of the HNF1A DNA binding domain complexed with DNA (Research Collaboratory for Structural Bioinformatics Protein Data Bank identifier 1IC8) (14).…”
Section: In Silico Modeling Of Pathogenicitymentioning
confidence: 99%
“…The impact of p.A251T on HNF1A function was assessed by using a suite of in vitro assays, as described previously (11). This impact on function was compared with that of wild-type HNF1A and two DNA binding domain mutations that cause MODY.…”
Section: In Vitro Functional Characterizationmentioning
confidence: 99%